Structure of transmembrane pore induced by Bax-derived peptide: Evidence for lipidic pores - Qian, Shuo (National Academy of Sciences, 2008)
The structures of transmembrane pores formed by a large family of pore-forming proteins and peptides are unknown. These proteins, whose secondary structures are predominantly α-helical segments, and many peptides form pores in membranes without a crystallizable protein assembly, contrary to the family of β-pore-forming proteins, which form crystallizable β-barrel pores. Nevertheless, a protein-induced pore in membranes is commonly assumed to be a protein channel. Here, we show a type of peptide-induced pore that is not framed by a peptide structure. Peptide-induced pores in multiple bilayers were long-range correlated into a periodically ordered lattice and analyzed by X-ray diffraction. We found the pores induced by Bax-derived helical peptides were at least partially framed by a lipid monolayer. Evidence suggests that the formation of such lipidic pores is a major mechanism for α-pore-forming proteins, including apoptosis-regulator Bax.